IDENTIFICATIONANDCONTROL OF NONLINEAR SYSTEMS USING MULTIPLE GENERALIZED PREDICTIVE CONTROL BASED NEURO-FUZZY MODEL - NGUYEN , TUAN HUNG (2014)
This thesis presents an approach of identification and control of nonlinear processes by using Multiple Generalized Predictive Control (MGPC) based Neurofuzzy model. Firstly, the dynamic characteristics of a nonlinear system is identified by a Neuro-fuzzy model which is formulated as an alternative form as multiple linear Auto-Regressive Exogenous (ARX) sub models. Subsequently, the MGPC are designed in which each GPC is based on the sub ARX model working cooperatively with other GPCsto control the nonlinearsystem.